PENGEMBANGAN MODEL PEMBELAJARAN BERMAIN KREATIF DAN KOORDINASI TERHADAP KETERAMPILAN GERAK (MOTORSKILLS) MAHASISWA PENDIDIKAN OLAHRAGA - Sri Rizki Handayani; Muhammad Ramli (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2018)
In general, the purpose of this research and development is to produce a model of learning motor skills through creative play and coordination. In addition, research and development is to empower of thinking, life skills psychomotor and in particular on the basic motion sports education in accordance with their duties according to the characteristics of theoretical concepts. The draft research and development (R & D). Subjects were students of Muhammadiyah Sorong STKIP Sports Education courses. This research steps: (1) analysis of needs; (2) the expert evaluation (initial product evaluation); (3) test cobs limited (small group trial); (4) The main trial. Analysis of data using quantitative descriptive,and outcome effectiveness model used statistical tests using t-test formula t-hit. Based on the results of the development can be concluded that: (1) the development of models of learning through creative play and coordination is very helpful for students sports education in empowering thinking skills, life skills psychomotor and learning outcomes motor skills (motor skills) was good especially the basic motion sport suit the characteristics of growth and the development of motor skills (motor skills); (2) based on the effectiveness of the test results with the results of the t-test with a t-test = 22.820, df = 44 and p-value = 0.00> 0.05 indicates a very significant improvement. So the development of creative play learning model and the coordination of motor skills effective sports education student to achieve the goal.